Reading Difficulties Faced by Students in the Implementation of Bilingual Books in the University Level - Addas, Reski Kartini (Journal of Humanity Studies, 2022)
Reading is part of the productive skill in learning English and it is important like other skills which learners have to master all skill. That skill has many issues for the learners especially to the English Foreign Language (EFL) learners because reading is not easy to learn. The purpose of this mini-research is to investigate various reading difficulties are faced by the students in science classrooms and to find out what strategies they use to overcome reading difficulties. A questionnaire and essay were distributed and for collecting data, a survey questionnaire and an essay were done on thirty students from different departments in the Faculty of Science. The results obtained from the survey questionnaire and essay answer the research questions. The findings show that students face problem-related in reading comprehension. These problems are related to the poor habit of reading and lack of interest in reading by using bilingual books in the classroom. So, the students need more interactive learning activities in the class as their strategies to solve their problems in facing reading difficulties.